Perbandingan User Experience Aplikasi Tiket.com dan Pegipegi Menggunakan Metode User Experience Questionnaire - Rizki Ade Ningsih; Ken Ditha Tania (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Advances in information technology make many human activities easier and faster. One form of information technology advancement that exists is the existence of a mobile application that can help users and management companies carry out various business processes online. Over time, people began to use applications to meet their daily needs, including the need to travel, such as booking travel tickets and hotels. One of the existing travel and hotel applications is Tiket.com and Pegipegi. Both of these applications offer the same services, making the competition even tougher. This research was conducted to compare user experiences from Tiket.com and PegiPegi using the User Experience Questionnaire (UEQ) method by measuring the attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty scales. The results showed that all UX scales from Tiket.com received positive evaluations. Whereas in Pegipegi, the attractiveness, perspicuity, efficiency, dependability, and stimulation scales received positive evaluations, but the novelty scale received neutral evaluations. From the results of the user experience comparison between Tiket.com and Pegipegi, Tiket.com gets a slightly higher user experience value than Pegipegi on all UEQ scales, but there is no significant difference for all scales.